Comparison between Certain Equivalent Norms Regarding Some Familiar Properties Implying WFPP - Helga Fetter; Berta Gamboa de Buen (International Journal of Mathematics and Mathematical Sciences)
In a Banach space with a basis we define a similar norm to the norm shown by Lin to make l1 into a space with FPP and make a comparative study of certain geometric properties such as the Opial property, WNS, and uniform nonsquareness of the original space and the space with the new norm.